Interpretative doubts in the context of rgulations regarding the tax on the income of controlled foreign entities - Dominika Wróblewska (Prawo Budżetowe Państwa i Samorządu)
The main purpose of the publication is to determine the role and significance of the tax on income of the CFC generated by a taxable person as a taxation mechanism aimed to tax income earned by foreign entities controlled by Polish taxpayers, based in countries with more preferential tax regulations than Poland. The article indicates the possible inaccuracies and doubts caused by the CFC regulations and their interpretation. The aim of the article is also an attempt to assess the effectiveness of the abovementioned regulations, taking into account the revenue of the state budget from the taxation of controlled foreign companies. The remarks included in the study were prepared using the analytical and dogmatic-exegetical methods, mainly based on the interpretation of the provisions of the PIT Act and the CIT Act, as well as views of the doctrine. The Operational reports are the source of empirical data on the implementation of the state budget in 2015–2018.